Variability and predictability of winter cold nights in Argentina - Collazo, Soledad Maribel (2019)
Extreme cold events can cause crop damage as well as an increase in energy demand and even in the mortality rate. Identifying the atmospheric processes associated with the occurrence of these extremes would allow decision-makers to implement preventive and mitigation actions. The goal of this study is to identify predictors of cold extremes of minimum temperature during winter in Argentina (north of 40 °S), and their modulation by the different El Ni~no-Southern Oscillation (ENSO) phases for the period 1970?2015. Lagged correlation analysis between winter cold nights and several global and regional climate indices identified ENSO, subtropical jet intensity, position and intensity of the South Pacific Anticyclone (SPA), and a blocking index as the dominating forcings. The El Niño phase is associated with a decrease in the occurrence of cold extremes. In addition, an increase in the number of blocking events together with a weaker subtropical jet and, a less intense and northward shift of the SPA also inhibit the occurrence of cold extremes of the minimum temperature. Our results indicate persistence in the winter cold nights series compared with the previous season in eastern Argentina. Twowinters with opposite extreme conditions (high and low frequency of cold nights) were selected as case studies. Since both cases occurred under ENSO neutral conditions, we also searched for cold nights predictors consideringonly neutral years. We detected the presence of an equivalent barotropic structure located in southeastern Pacific in both events, which confirmed the importance of the SPA intensity and blocking events as predictors in absenceof an active El Niño.